Author reply: aligning relations with faces, words, and emotions - Parkinson, B (SAGE Publications, 2021)
How do facial movements and verbal statements relate to emotional processes? A familiar answer is that the primary phenomenon is an internally located emotion that may then get expressed on the face and represented in words. In this view, emotion’s social functions and effects are indirect consequences of prior intrapsychic states or events. By contrast, my target article argued that facial and verbal activity are constituents rather than consequences of the dynamic production of fundamentally relational emotions. This article clarifies this alternative position and evaluates potential counterarguments.